2010
DOI: 10.1186/1472-6807-10-36
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of binding properties and specificity through identification of the interface forming residues (IFR) for serine proteases in silico docked to different inhibitors

Abstract: BackgroundEnzymes belonging to the same super family of proteins in general operate on variety of substrates and are inhibited by wide selection of inhibitors. In this work our main objective was to expand the scope of studies that consider only the catalytic and binding pocket amino acids while analyzing enzyme specificity and instead, include a wider category which we have named the Interface Forming Residues (IFR). We were motivated to identify those amino acids with decreased accessibility to solvent after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This assumption leads to the conclusion that polypeptides also inhibit elastase in a competitive way using Michaelis-Menten kinetics, since the residue between Thr and Ahp units presumably defines the specificity toward specific serine proteases (Matern et al, 2003b;Yamaki et al, 2005;Salvador et al, 2013). Through identification of the IFR (interface forming residues) for serine proteases in silico docked to different inhibitors, it was concluded that the serine proteases interfaces prefer polar residues (with some exceptions) (Ribeiro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption leads to the conclusion that polypeptides also inhibit elastase in a competitive way using Michaelis-Menten kinetics, since the residue between Thr and Ahp units presumably defines the specificity toward specific serine proteases (Matern et al, 2003b;Yamaki et al, 2005;Salvador et al, 2013). Through identification of the IFR (interface forming residues) for serine proteases in silico docked to different inhibitors, it was concluded that the serine proteases interfaces prefer polar residues (with some exceptions) (Ribeiro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A construct “nanoenvironment” was previously defined in our earlier work regarding the characterization for the specificity of ligand binding, protein function preservation in mutants and the specificity of enzymes based on the type of interface residues (Fernandez et al, 2003 [29]; Marcellino et al, 1996 [30] and Ribeiro et al, 2010 [31], respectively). As defined by Murakami et al (2005)[2], His12 and His47 are the key catalytic residues, followed by the metal ion coordinating residues Glu32, Asp34 and Asp91.…”
Section: Methodsmentioning
confidence: 99%
“…In this approach, both the ligand and the receptor have very stiff structures, thereby the name rigid body docking. Although simplistic, the method was successfully used for the analysis of the serine proteases specificity 7 .…”
Section: Introductionmentioning
confidence: 99%